The Impact Of Toserba Abdussalam On Economic Activities - M. Basri; Baisuni; Fatimah; Siti Solihah; Siti Khoirunnisa; Kholilah (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The presence of modern retail outlets in rural areas has the potential to influence the economic dynamics of MSME operators. This study aims to analyse the impact of the Abdussalam Supermarket on the economic activities of MSMEs in Pasak Village. The study employs a descriptive approach using both quantitative and qualitative methods through observation, interviews, and questionnaires administered to MSME operators in the vicinity of the supermarket. Data were analysed using descriptive statistics, pre- and post-test comparisons regarding the supermarket’s presence, and linear regression analysis. The results indicate that the Abdussalam Supermarket has a dual impact. Its presence enhances business efficiency through easier access to raw materials, price stability, and local economic circulation; however, it also creates competition, leading to a decline in turnover for some SMEs. These findings suggest that the adaptability of business operators is a key factor in determining the economic impact experienced. The study concludes that the Abdussalam Supermarket acts as both a driver and a challenge for SMEs. Synergy between the supermarket management, SME operators, and the village government is required to optimise positive impacts and support sustainable local economic growth.